Complementary and alternative medicine use among Chinese and white Canadians - Quan, Hude (College of Family Physicians of Canada, 2008)
OBJECTIVE: This study aimed to describe the level of complementary and alternative medicine (CAM) use and the factors associated with CAM use among Chinese and white Canadians. DESIGN: A cross-sectional telephone survey conducted in English, Cantonese, and Mandarin. SETTING: Calgary, Alta. PARTICIPANTS: Chinese and white residents of Calgary aged 18 or older. MAIN OUTCOME MEASURES: Rates of use of 11 CAM therapies, particularly herbal therapy, massage, chiropractic care, and acupuncture; reasons for use of CAM therapies. RESULTS: Sixty percent of 835 Chinese respondents (95% confidence interval [CI] 56.5% to 63.2%) and 59% of 802 white respondents (95% CI 55.1% to 62.0%) had used CAM in the past year. Chinese respondents were more likely to use herbal therapy than white respondents were (48.7% vs 33.7%, P < .001), less likely to use massage (17.1% vs 30.4%, P < .001) and chiropractic care (8.4% vs 21.2%, P < .001), but equally likely to use acupuncture (8.3% vs 7.9%, P = .173). The common factor associated with herbal therapy, acupuncture, or massage use among Chinese and white respondents was receiving a CAM recommendation from a family member or friend. Factors unique to either Chinese or white CAM users varied by therapy. For example, herbal therapy use for Chinese respondents was associated with the presence of chronic disease (adjusted odds ratio [AOR] 2.15, 95% CI 1.09 to 4.24 for having 3 diseases compared with those without chronic disease), beliefs about the effectiveness of herbal therapy (AOR 1.56, 95% CI 1.12 to 2.17), and trust in herbal therapy practitioners (AOR 1.72, 95% CI 1.24 to 2.37). Herbal therapy use for white respondents was associated with the beliefs that herbal treatment had fewer side effects than prescription drugs (AOR 1.81, 95% CI 1.31 to 2.50) and that herbalists took a holistic approach (AOR 2.07, 95% CI 1.49 to 2.87). CONCLUSION: While the percentage of CAM use was similar in both groups, Chinese Canadians mainly used herbal therapy and white Canadians used a range of CAM therapies. Factors associated with CAM use varied with ethnicity and type of CAM therapy. Presence of chronic disease, however, was an important factor for Chinese Canadians. That finding suggests that Chinese Canadians use CAM for the treatment of chronic disease, while white Canadians use such therapies for disease treatment and health maintenance.